Highways : the location,design, construction and maintenance of road pavements - O'Flaherty, Coleman A.; Boyle, A.
Highways' is a comprehensive textbook on all aspects of road engineering. This new edition, written by a team of acknowledged experts in the field, teams up with 'Transport Planning and Traffic Engineering' to become a worthy successor to O'Flaherty's classic 'Highway Engineering' set. This fourth edition covers road location and plans, roadwork materials, surface and subsurface moisture control, pavement design and construction, thickness design of bituminous and concrete pavements and road maintenance and rehabilitation. The content has been expanded and thoroughly updated to take into accou.